Due diligence in Polish civil law in the aspect of individual legal practice of the profession of attorney (comparative analysis of Polish and US legal systems) - Mielewczyk, Dominik Damian (Studia Iuridica Toruniensia, 2021)
The Author of the article conducts an analysis of the concept of due diligence in Polish and US civil law in the aspect of individual legal practice of the profession of attorney. The study concerns the discussion of the liability in the subject matter and the legal regime that is created by the key articles of Polish Civil Code, views of Polish judicial decisions and the US judicial decisions. Herein an attention has been devoted to the problem of the definition and demarcation of the semantic range of the due diligence clause, opinions of the doctrine and judicature and the practical issues. This paper includes the attempts of the author to indicate the relevant circumstances which give the rise to civil liability for legal malpractice.